A multi-perspective approach to service quality assessment and analysis in hospitals for service improvement and stakeholder satisfaction - Bautista, Joy Mari Sebastian (Animo Repository, 2013)
The health care service industry carries an intense pressure to maintain quality in all aspects of service given that quality health care translates to quality human welfare. Thus, service quality in health care becomes a very critical matter that must be constantly assessed and analyzed. Health care service quality is greatly affected by the key stakeholders, namely the patients, health professionals, management as well as the health care regulators, who comprise the system in determining and characterizing health care services according to their role, interests and influence within a health facility. With this, the need for an integrated service quality framework in health care, especially in hospitals where most services are offered, has been recognized. The different perspectives of the key stakeholders have to be incorporated in assessing service quality and even in analyzing advantageous strategies for improving service dimensions. Through this, the satisfaction of not just the service recipients, as existing service quality frameworks have proposed, but all of the important stakeholders in health care can be ensured, which can then lead to a long-term assurance of quality health care services. As such, this study aims to create an operationalized framework in health care service quality that not only integrates the different perspectives of these key stakeholders but also analyzes the potential root causes of and even possible solutions to issues within service dimensions so as to have a better focus on service improvements that can bring about stakeholder satisfaction. Given this objective, the integrated service quality assessment framework developed based on literature resulted in a hierarchical form that branches out from three basic service categories – i.e. Service Structure, Service Process and Service Outcome. This initial framework then needed to be further validated through an actual application in a hospital setting using a survey instrument, wherein measurement of hospital service quality in the perspectives of the patients, health professionals and hospital management personnel was made possible by getting sample sizes from each group of stakeholders as survey respondents. From this survey, the personal opinion and evaluations of each group of stakeholders about the service quality and their satisfaction level over the hospital service dimensions from the proposed framework have been obtained and summarized. The data gathered have then been used to statistically validate the framework via Structural Equation Modeling (SEM). Structural Equation Modeling or SEM became necessary for the purpose of this study, as it seeks to indicate which among the dimensions proposed are statistically significant and what other dimensions each is related to. As such, after running SEMs per stakeholder, results revealed that all the dimensions proposed are significant to each stakeholder. Most correlations had loadings of 0.7 and above that signify very strong relationships between the indicators and their corresponding dimensions, while the rest had loadings of 0.5 to 0.69 that denote substantial relationships. With these results, qualitative data gathering through more in-depth interviews had also been conducted in order to further verify the results and streamline the proposed framework based on what is really important to each stakeholder in their own definitions of hospital service quality. The validations done in this study have streamlined the initial framework into a final integrated framework. These have also made it possible to extend the study into proposing distinct sub-frameworks for each stakeholder in the event that a need to further assess the perspective of a particular dissatisfied group of stakeholders arises. All in all, the framework proposed has proven the hypothesis of how the service structure of a hospital encompasses all the other aspects of service, as it can directly affect both the service process and service outcome of a hospital. With the consent of two host tertiary-level private hospitals in Metro Manila (i.e. De Los Santos Medical Center in Quezon City and Las Piñas Doctors Hospital in Las Piñas City) for the framework to be tested and operationalized in their premises, the study had also demonstrated how important it is to focus on the administrative service within a hospital given that this particular dimension acts as an independent or exogenous variable that can influence the quality of all the other hospital service dimensions in the final service quality assessment framework.